2014
DOI: 10.3892/mmr.2014.2155
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs mediate oleic acid-induced acute lung injury in rats using an alternative injury mechanism

Abstract: Intravenous (IV) infusion of oleic acid (OA) distributes OA microemboli in the pulmonary capillaries, which results in severe vascular congestion, hemorrhage vascular congestion, interstitial edema, intravascular coagulation and bleeding. The immune response to acute lung injury (ALI) is known to be associated with rapid and widespread changes in microRNA (miRNA) expression in the lung. The present study of a model of rat lung injury aimed to investigate how the lung miRNA profile changes to mediate ALI. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
(29 reference statements)
3
16
0
Order By: Relevance
“…Lee et al reported that miR-21 was also upregulated throughout the 24 h following OA challenge, with a time-course analysis of miRNA expression in rat OA-induced ALI. 47 These in vitro and in vivo results suggest the importance of miR-21 in ALI. Coincidently, we also found an increase in miR-21 serum concentrations in ARDS patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lee et al reported that miR-21 was also upregulated throughout the 24 h following OA challenge, with a time-course analysis of miRNA expression in rat OA-induced ALI. 47 These in vitro and in vivo results suggest the importance of miR-21 in ALI. Coincidently, we also found an increase in miR-21 serum concentrations in ARDS patients.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with previous studies that upregulated miR-21 depressed PTEN mRNA and protein expression in ventilator-induced and OA-stimulated rat ALI model. 47,49 In addition, PTEN contains miR-21-binging site within 3′ UTR. 45 Hence, we provide evidence linking LPS-mediated upregulation of miR-21 with downregulation of PTEN mRNA and protein in alveolar epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few miRNA studies also reported either up/or down‐regulated miRNAs expression (Table ) consistent with ALI (Guo et al, ; Huang et al, ; Lee et al, ; Tan et al, ; Li et al, ; Otsuki et al, ; Rao et al, ), but the functional role of those miRNAs has not been studied either in vivo and/or in vitro conditions. Overall, these studies suggest the regulatory roles of miRNAs in controlling inflammatory target gene expression in ALI/ARDS and that a small change in miRNA expression could result in marked phenotypic consequences.…”
Section: Regulatory Role Of Mirnas In the Pathogenesis Of Ali/ardsmentioning
confidence: 99%
“…Additionally, it was found that pulmonary miRNA expression varies depending on the specific mechanism of lung injury. MiRNA expression patterns have been analyzed in lung injury caused by mechanical ventilation [7779], by administration of oleic acid [80], induced by pathogens including endotoxin exposure [8184] or induced by radiation or hyperoxia [85, 86]. In vitro studies using cyclic mechanical stretch modeling mucosal injury showed changes in epithelial miRNAs expression [87].…”
Section: Mirnas In Mucosal Immune Functionsmentioning
confidence: 99%